On the way to a new audit culture: Innovative grading at the Private University of Education Diocese of Linz (Pedagogical Horizons, 2021)
In this paper, international publications on Innnovative Grading are presented, discussed and supplemented with current research of master students of the Private University of Education Diocese of Linz. Thereby, the initiative of the project group Innovative Grading will be continued. From that, the legitimization of Innovative Grading as an equivalent form of assessment to the conventional numerical grading system is derived.
Keywords: innovative grading; critic on the conventional numerical grading system; performance evaluation; quality management